Clinical characteristics, management and 1-year outcomes of patients with acute coronary syndrome in Iran: the Iranian Project for Assessment of Coronary Events 2 (IPACE2). Issue 12 (15th December 2015) - Kassaian, Seyed Ebrahim; Masoudkabir, Farzad; Sezavar, Hashem; Mohammadi, Mohammad; Pourmoghaddas, Ali; Kojouri, Javad; Ghaffari, Samad; Sanaati, Hamidreza; Alaeddini, Farshid; Pourmirza, Bahin; Mir, Elham
Abstract : Objectives: To assess contemporary data on characteristics, management and 1-year postdischarge outcomes in Iranian patients hospitalised with acute coronary syndrome (ACS). Setting: 11 tertiary care hospitals in 5 major cities in the Islamic Republic of Iran. Participants: Patients aged ≥20 and ≤80 years discharged alive with confirmed diagnosis of ACS including ST-segment elevation myocardial infarction (STEMI), non-STEMI (NSTEMI) and high-risk unstable angina (HR-UA). Primary and secondary outcome measures: Patients were followed up regarding the use of medications and the end points of the study at 1 month and 1 year after discharge. The primary end point of the study was 1-year postdischarge major adverse cardiac and cerebrovascular events (MACCEs), defined as mortality (cardiac and non-cardiac), ACS and cerebrovascular attack (stroke and/or transient ischaemic attack). The secondary end points were hospital admission because of congestive heart failure, revascularisation by coronary artery bypass grafting surgery or percutaneous coronary intervention (PCI), and major and minor bleeds. Results: A total of 1799 patients (25.7% STEMI and 74.3% HR-UA/NSTEMI) discharged alive with confirmed diagnosis of ACS were included in the final analysis. During hospitalisation, the majority of the patients received aspirin (98.6%), clopidogrel (91.8%), anticoagulants (93.4%), statins (94.3%) and β-blockers (89.3%). Reperfusion therapy was performed in 62.6% of patients with STEMI (46.3% thrombolytic therapy and 17.3% primary PCI). The mean door-to-balloon and door-to-needle times were 82.9 and 45.6 min, respectively. In our study, 64.7% and 79.5% of the patients in HR-UA/NSTEMI and STEMI groups, respectively, underwent coronary angiography. During the 12 months after discharge, MACCEs occurred in 15.0% of all patients. Conclusions: Our study showed that the composition of Iranian patients with ACS regarding the type of ACS is similar to that in developed European countries and is unlike that in developing countries of the Middle East and Africa. We found that our patients with ACS are treated with high levels of adherence to guideline-recommended in-hospital medications.